Resort Alam Bukit Sekipan Tawangmangu - Durrun Nafis, Moh; , Ir.Alpha Febela P. MT (2016)
The development and utilization of natural potential in Sekipan Tourism Complex located in the village of the District Kalisoro Tawangangmangu not optimal. lack of means to know more details about how the process of producing vegetables and fruits are fresh and tasty for consumption, while the process requires a fairly long time and did not rule dibutuhkanya accommodation in the form of accommodation, to support such activities. Seeing the conditions that exist, it is necessary to encourage tourism facility and infrastructure improvement. The presence of the design of a resort worthy travelers to stay while enjoying the potential of rural areas by Design resorts that use environmentally friendly building materials approach. so the resort development to support tourism activities in the region and can increase the number of tourists and prolong the stay of tourists in the region. Methods used in this research observation techniques, engineering studies and engineering studies literature and material documents to analyze data. Resort Alam Bukit Sekipan Tawangmangu is a design that combines elements of nature natural travel with an architecture that uses the approach of environmentally friendly materials, so the resort was found that respects the environment.